2001
DOI: 10.3136/fstr.7.45
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Aroma Components of Tosa-buntan(Citrus grandis Osbeck forma Tosa) Fruit.

Abstract: The volatile components of Tosa-buntan (Citrus grandis Osbeck forma Tosa) cold-pressed peel oil were studied by GC and GC-MS. The characteristic aroma compounds were investigated by GC-olfactometry in which a semi-bore capillary column, DB-Wax, was used for effective separation of the volatile components of the oil. Hydrocarbons including mono and sesquiterpenes of the oil accounted for about 98% of the volatile components. The characteristic flavor was also present in the oxygenated fraction. Flavor dilution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 23 publications
1
26
1
Order By: Relevance
“…Conventional methods of extraction show that the concentration of limonene in C. grandis peel is 72.31 − 94.8% in samples from different geographic origins (Khan et al, 2007, Sawamura et al, 2001, Njoroge et al, 2005. However, in the present study, limonene was 18.67% in whole fruits of dangyuja, whereas it was 3.41% and 12.14% in phalsak and yeagam respectively.…”
Section: Gc-ms Analysis Chromatographic Analysis Was Carried Out Usincontrasting
confidence: 52%
See 2 more Smart Citations
“…Conventional methods of extraction show that the concentration of limonene in C. grandis peel is 72.31 − 94.8% in samples from different geographic origins (Khan et al, 2007, Sawamura et al, 2001, Njoroge et al, 2005. However, in the present study, limonene was 18.67% in whole fruits of dangyuja, whereas it was 3.41% and 12.14% in phalsak and yeagam respectively.…”
Section: Gc-ms Analysis Chromatographic Analysis Was Carried Out Usincontrasting
confidence: 52%
“…c) relative peak area percentage (peak area relative to the total peak area %) d) −, not detected. citronellal, linalool, β-caryophyllene, α-terpineol, and nootkatone are common among different geographically located samples (Sawamura et al, 2001;Njoroge et al, 2005). Additionally, γ-sitosterol, stigmasterol, and tengeretin as well as free fatty acids and their esters previously reported in immature dangyuja fruits (Lim et al, 2009), were also found in the supercritical extract of mature fruits in this study.…”
Section: Gc-ms Analysis Chromatographic Analysis Was Carried Out Usinmentioning
confidence: 49%
See 1 more Smart Citation
“…Tomi et al (2008) reported the use of essential oils in determining hybrid status by comparing oil profiles between hybrid plants and their putative parents. Previous studies on the use of essential oils for clarifying taxonomic status and hybrid identification on Citrus have been reported (Sawamura et al, 2001;Gogorcena and Ortiz, 2006;Tao et al, 2008). In this study, the variability of essential oil composition among 40 samples of Indonesian C. maxima cultivars and landraces was examined along with their taxonomic implication in defining infraspecific grouping within the species.…”
Section: Introductionmentioning
confidence: 99%
“…Reserach on Citrus essential oils are generally conducted in relation to their aromatic properties applied in food industry, cosmetics and perfume (Sawamura et al, 2001;Gogorcena and Ortiz, 2006;Tao et al, 2008). Several studies revealed the use of essential oils from various plant species as food preservatives, antimicrobial agent and natural pesticides.…”
Section: Introductionmentioning
confidence: 99%